FRI0160 Evaluation of inflammatory cardiovascular (CV) risk factors in pre- and post-menopausal female patients with rheumatoid arthritis (RA). (15th June 2017) - Garmish, OO; Levchenko, V; Kovalenko, V
Abstract : Objectives: To assess inflammatory factors and peripheral vessels involvement as markers of cardiovascular risk in female patients with RA Methods: 105 female patients who fulfill ACR/EULAR 2010 criteria were examined. Laboratory assessments consisted of biochemistry and hematology analysis, measuring of CRP level, rheumatoid factor, anti-CCP level, total cholesterol, HDL, LDL, thyroglobulin, apoliprotein, A1, apoliprotein B, uric acid, HbA1c, microalbuminuria. DAS28 was used in characterizing RA activity. CV risk was defined per mSCORE. Tibial artery and carotid artery ultrasonography examination included the measurement of cIMT in 3 points, detection of focal plaques in the extracranial carotid tree, blood flow velocity and morphology of the intima was performed Results: 83.3% reproductive age patients were without CV risk, 11.1% experienced middle level and 5.6% low level of CV risk on mSCOR. In 96.1% postmenopausal patients moderate, high and very high CV risk was detected. According to multiple logistic regression analysis we identified CV risk factors: high CRP and DAS28, swollen joint count, LDL cholesterol level, menopause, thickness of cIMT and tibial artery. Were identify a significant correlation between tibial artery thickness and age, BMI, RA duration, systolic and diastolic blood pressure, cholesterol, menopause (p<0.01, χ2=26.18). Also, we identified a significant relationship between tibial artery thickness and changes of the intima morphology (χ2=31, 64; p<0, 01), carotid plaques (χ2=26, 179; p<0, 01), sclerosis of the heart valves (χ2=25, 78; p<0, 01). A less significant relationship was between cIMT (χ2=8, 507; p<0, 01). The DAS28, age (p<0.001), thickness of cIMT and tibial artery (p<0.001) are predictive factors for the development of carotid plaques. The predictive factors for tibial artery thickness in female patients <45 age are: high CRP (p<0.004) and DAS28 (p<0.03), anti-CCP positivity (p<0.04), Vps internal carotid artery (p<0.04) Conclusions: The results of our study indicate that high CRP and DAS28 score, swollen joint count, LDL cholesterol level, menopause, thickness of cIMT and tibial artery associated with the increased cardiovascular risk. Tibial artery thickness and Vps internal carotid artery may be assessed like the new predictive factors of CV diseases in RA female patient Acknowledgements: None Disclosure of Interest: None declared